Targeting thrombospondin-2 retards liver fibrosis by inhibiting TLR4-FAK/TGF-β signaling - Ning Zhang; Xiaoning Wu; Wen Zhang; Yameng Sun; Xuzhen Yan; Anjian Xu; Qi Han; Aiting Yang; Hong You; Wei Chen (JHEP Reports, 2024)
Background & Aims: Thrombospondin-2 (THBS2) expression is associated with liver fibrosis regardless of etiology. However, the role of THBS2 in the pathogenesis of liver fibrosis has yet to be elucidated. Methods: The in vivo effects of silencing Thbs2 in hepatic stellate cells (HSCs) were examined using an adeno-associated virus vector (serotype 6, AAV6) containing short-hairpin RNAs targeting Thbs2, under the regulatory control of cytomegalovirus, U6 or the α-smooth muscle promoter, in mouse models of carbon tetrachloride or methionine-choline deficient (MCD) diet-induced liver fibrosis. Crosstalk between THBS2 and toll-like receptor 4 (TLR4), as well as the cascaded signaling, was systematically investigated using mouse models, primary HSCs, and human HSC cell lines. Results: THBS2 was predominantly expressed in activated HSCs and dynamically increased with liver fibrosis progression and decreased with regression. Selective interference of Thbs2 in HSCs retarded intrahepatic inflammatory infiltration, steatosis accumulation, and fibrosis progression following carbon tetrachloride challenge or in a dietary model of metabolic dysfunction-associated steatohepatitis. Mechanically, extracellular THBS2, as a dimer, specifically recognized and directly bound to TLR4, activating HSCs by stimulating downstream profibrotic focal adhesion kinase (FAK)/transforming growth factor beta (TGF-β) pathways. Disruption of the THBS2-TLR4-FAK/TGF-β signaling axis notably alleviated HSC activation and liver fibrosis aggravation. Conclusions: THBS2 plays a crucial role in HSC activation and liver fibrosis progression through TLR4-FAK/TGF-β signaling in an autocrine manner, representing an attractive potential therapeutic target for liver fibrosis. Impact and implications: Thrombospondin-2 (THBS2) is emerging as a factor closely associated with liver fibrosis regardless of etiology. However, the mechanisms by which THBS2 is involved in liver fibrosis remain unclear. Here, we showed that THBS2 plays a prominent role in the pathogenesis of liver fibrosis by activating the TLR4-TGF-β/FAK signaling axis and hepatic stellate cells in an autocrine manner, providing a potential therapeutic target for the treatment of liver fibrosis.